2001
DOI: 10.1007/s100720170060
|View full text |Cite
|
Sign up to set email alerts
|

Which target for DBS in Parkinson's disease? Subthalamic nucleus versus globus pallidus internus

Abstract: We selected 14 patients with advanced idiopathic Parkinson's disease (PD) and examined the clinical effects of STN DBS versus GPi DBS. Nine patients underwent bilateral STN DBS and five underwent bilateral GPi patients. All patients were followed for at least 12 months. The evaluation was performed on and off drug before surgery; on-drug/on-DBS and off-drug/on-DBS at 1, 3, 6 and 12 months after stereotactic surgery. At 1 and 3 months after surgery in off-drug/on-DBS condition, both groups showed an improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…As such, it is difficult to compare the results from the two sites. These results and those of other studies of stimulations of the subthalamic nucleus have been consistently robust with most studies showing 45-55% improvement and some showing as high as 60-70% improvement in "off" medicine motor subscore 57,58,[60][61][62][80][81][82] . Study of 42 patients followed up for five years showed that improvement seems to be stable with continued efficacy and a 54% improvement in "off" motor score 80 .…”
Section: Subthalamus Nucleus Stnsupporting
confidence: 70%
See 1 more Smart Citation
“…As such, it is difficult to compare the results from the two sites. These results and those of other studies of stimulations of the subthalamic nucleus have been consistently robust with most studies showing 45-55% improvement and some showing as high as 60-70% improvement in "off" medicine motor subscore 57,58,[60][61][62][80][81][82] . Study of 42 patients followed up for five years showed that improvement seems to be stable with continued efficacy and a 54% improvement in "off" motor score 80 .…”
Section: Subthalamus Nucleus Stnsupporting
confidence: 70%
“…The results of one study of the bilateral globus pallidus DBS in 11 patients followed up for up to five years showed that dyskinesias remained significantly reduced until the last assessment, but initial improvement of "off"-period motor symptoms and fluctuations was not sustained and gradually declined 59 . Whether or not this study is representative of the long-term effect of DBS of the internal globus pallidus requires further study in more patients.In contrast to thalamotomy or Vim DBS, GPi DBS has reliably alleviated all cardinal motor symptoms of Parkinson's disease including akinesia, brandkinesia, rigidity, tremor and gait 39,57,58,[60][61][62][63][64][65][66][67] . DBS of GPi improves "off" dystonia 68,69 and, like pallidotomy, has a strong, direct, suppressing effect on levodopainduced dyskinesias 39,58,65,[70][71][72] .…”
Section: Globus Pallidus Internus Gpimentioning
confidence: 99%
“…Only a few studies have tried to directly compare GPi and STN DBS [32][33][34][35][36]. However, most of these studies were not randomized and they had relatively small sample sizes.…”
Section: Globus Pallidus or Subthalamic Stimulation?mentioning
confidence: 98%
“…Improvement in UPDRS motor scores was greater in the STN group (67%) compared with the GPi group (54%). Scotto di Luzio et al [35] compared nine patients with STN DBS to five patients with GPi DBS. STN DBS was demonstrated to be superior to GPI DBS both in the control of clinical features and the reduction in off time.…”
Section: Globus Pallidus or Subthalamic Stimulation?mentioning
confidence: 99%
“…4 The choice of stimulation target has evolved since and studies have reported positive effects of DBS on locomotion and postural stability, following stimulation of the STN, [24][25][26][27]2,14,28 SNr, 29 cortex, 30,31 thalamic Vim, 32 and zona incerta, 33 to name but a few. Today, multiple stimulations ͑e.g., STN + PPN͒ are emerging as a possibility to alleviate distal as well as axial signs.…”
Section: Introductionmentioning
confidence: 99%